Assessment of methanogen survival in anaerobic enrichment cultures degrading long-chain fatty acids - Salvador, A. F. (2011)
Long-chain fatty acids (LCFA) are generally considered highly toxic towards methanogens. However, high methane yields have been obtained from high-load anaerobic digestion of LCFA, suggesting that methanogens can tolerate these compounds. In this work, hydrogenotrophic and acetoclastic methanogens were added to LCFA-degrading enrichments in order to evaluate their survival in the presence of unsaturated-LCFA (C18:1, oleate) and saturated-LCFA (C16:0, palmitate). Two hydrogenotrophs (Methanobacterium formicicum and Methanospirillum hungatei), and two acetoclasts (Methanosarcina mazei and Methanosaeta concilii) were tested. Oleate- and palmitate-enrichment cultures (OM and PM, respectively) were amended with each of the methanogens and incubated with 1 mM of the corresponding LCFA. Survival of methanogens after several transfers was evaluated by PCR-DGGE. For the hydrogenotrophs, results showed that M. formicicum survived in both OM and PM cultures, while M. hungatei only grew in the PM culture. Moreover, viability tests using live/dead staining coupled to fluorescent microscopy observation and cell counting indicated that M. hungatei is indeed more sensitive to oleate than M. formicicum. The percentage of damaged cells, caused by the exposure to low concentration of oleate (i.e. 0.5 mM), was very high in the case of M. hungatei (79%) contrasting with M. formicicum that was only slightly affected by this LCFA (8%). Regarding acetoclastic methanogens, both tested species prevailed in OM and PM cultures, although more abundant in PM enrichment. These results suggest that oleate is a more toxic compound for methanogens than palmitate. Nevertheless, all the methanogens studied, except M. hungatei, were found in the OM cultures.